Reliability, Validity, and Responsiveness of the Incremental Shuttle Walk Test in Patients With Interstitial Lung Disease. Issue 6 (November 2018) - Singh, Sumedha; Moiz, Jamal Ali; Ali, Mir Shad; Talwar, Deepak
Abstract : Purpose: To determine the reliability, validity, and responsiveness of the incremental shuttle walk test (ISWT) in patients with interstitial lung disease (ILD). Methods: This was a cross-sectional longitudinal study. Patients (n = 27, 10 males; mean age ± SD, 61 ± 9.8 y) with ILD of any etiology, who participated in an outpatient pulmonary rehabilitation (PR) program, were recruited. Reliability was determined by comparing the distance covered in meters between the ISWT-1 and the ISWT-2. Validity was assessed by correlating the distance covered in the ISWT-1, with the maximum oxygen consumption ( O2max ) obtained through cardiopulmonary exercise testing and distance covered during the 6-min walk test (6MWT). Responsiveness was assessed by comparing the distance covered in the ISWT-3, undertaken after the completion of PR, to the ISWT-1. Results: The distance covered was equivalent between the ISWT-1 (216.7 ± 64.9 m) and the ISWT-2 (220.7 ± 67.3 m), with an excellent intraclass correlation coefficient (ICC2, 1 = 0.91; 95% CI, 0.81-0.95). The standard error of measurement and minimal detectable change at the 95% CI (MDC95 ) values for the ISWT were 19.5 m and 53.9m, respectively. There were significant correlations between the distance covered on the ISWT and O2max ( r = 0.79, P < .0001) and the distance covered on the 6MWT ( r = 0.76, P < .0001). Following PR, the change in the ISWT distance showed large effect size (ES = 0.85) and standardized response mean (SRM = 1.58). Conclusions: The ISWT is a reliable, valid, and responsive measure of estimated functional capacity in patients with ILD. Abstract : The present study assessed the reliability, validity, and responsiveness of the incremental shuttle walk test in patients with interstitial lung disease. The results of this study serve as a crucial clinical tool for clinicians to estimate the functional capacity of patients with interstitial lung disease.